Current understanding of the immune potential of B-cell subsets in malarial pathogenesis - Kalkal, Meenu; Das, Jyoti (Frontiers in Microbiology, 2023)
Abstract In the past several decades, our understanding of how B cells are generated and what function they perform has continued to advance. It is widely accepted that peripheral B cell subsetss play a critical role in mediating humoral immune responses. Surprisingly, human and murine malaria infections cause major alterations in composition of B cell subsets in both spleen and periphery. Multiple B cell subsets are well characterized in murine models following primary and secondary infection, although, in human malaria infection these subsets are not much defined. Further, Additionally, B cells have been shown to be able to secrete cytokines as well as present antigens to naive T cells. Maturation of B lymphocytes is a complex process which starts in the bone marrow and continues to develop in specific areas of secondary lymphoid organs. Furthermore, these peripheral B cell subsets play a putative role in B-cell mediated adaptive immune response. The rare known function of B cells includes the potential role in regulating the activities of other cells in the body as regulatory cells. Plasmodium infection strongly alter the frequency of these regulatory B cells indicating towards the immunoregulatory function of B cells in malaria. In malaria after exposure to the Plasmodium parasite, naive B cells get activated through B cell receptor (BCR) upon encounter to an antigen of the parasite. After activation these B cells undergo proliferation and further differentiation into peripheral B cell subsets such as marginal zone B cells, follicular B cells and memory B cells. It is important to note that these subsets, taken together, form the cellular basis of humoral immune responses, allowing protection against a wide array of Plasmodium antigens to be achieved. Although it remains a challenge and an important area of investigation to understand how these B cell subsets work together to provide protection against Plasmodium infection.